The impact of bequest taxation on wealth inequality: Theory and evidence - Berenice Anne Neumann; Niklas Scheuer (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2024)
We study the effect of bequests and their taxation on wealth inequality. We allow for random death and birth in a continuous-time, dynastic framework. Individuals behave optimally and accumulate wealth over their lifetime. Bequests above a tax exemption threshold are taxed according to a fixed rate. We derive a stochastic differential equation modeling dynastic wealth and obtain an analytical expression for the coefficient of variation. By calibrating our model to German wealth data, we utilize these analytical results to project empirical wealth inequality across various bequest tax rates and tax exemption thresholds. Most notably, our results indicate that a combination of a high tax exemption threshold paired with a high bequest tax rate reduces wealth inequality strongest when considering revenue-neutral alterations.
Keywords: D31; E21; H24; 330; wealth; bequest; taxation; wealth inequality; analytical solution